PERANCANGAN SISTEM INFORMASI INDEX PENYAKIT PASIEN RAWAT INAP MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI RSUD H. BOB BAZAR, SKM - Diana Sari; Rini Suwartika Kusumadiarti; Erix Gunawan (Sekolah Tinggi Pariwisata Mataram, 2023)
Medical record data processing at this time is not only done manually but also current technological developments also support data processing activities carried out using a computerized based system. Manual data processing has many weaknesses, besides requiring a long time, its accuracy is also unacceptable. Because the possibility of error is very large. The medical record contains information including personal identity, social and all other information concerning the patient. Processing of medical record indexing data at Bob Bazar Hospital has been integrated into SIMRS. However, inputting disease index data is still done by pulling patient diagnosis data one by one into Microsoft Excel from SIMRS. So that the data input takes quite a long time and the patient's disease index cannot be optimally processed to be used as a report. This study uses Microsoft Visual Studio 2010 at Bob Bazar Hospital. The system development method used is waterfall. Therefore, the author makes a configuration of the inpatient disease list data framework by utilizing Data Flow Diagrams (DFD) as a planning technique, Microsoft Visual Studio 2010 as an application program and Microsoft Access as an information base